SOCIAL SUPPORT AMONG VIETNAMESE UNIVERSITY STUDENTS: EVIDENCE OF GENDER DIFFERENCES - Ho, Thi Truc Quynh (Trường Đại học Đà Lạt, 2023)
Social support is considered to be an important element of relationships. Previous studies have provided evidence that low social support is closely related to poor physical and mental health. Gender has an important influence on social support for university students; however, research on the level of social support and differences in social support by gender for Vietnamese university students is still lacking. The current study aims to investigate the level of social support and gender differences in social support for Vietnamese university students. A total of 859 Vietnamese university students have completed the Perceived Social Support Scale (PSSS). The results revealed that Vietnamese university students have a high level of social support and that male students have a lower level of social support than female students. Factors that may contribute to gender differences in social support are discussed. These findings have important implications for the development of interventions to provide gender-based social support.